Komposisi dan Struktur Komunitas Fitoplankton di Danau Diatas Kabupaten Solok Sumatera Barat - Muhammad Ikhsan; Izmiarti Izmiarti; Indra Junaidi Zakaria (Universitas Andalas, 2015)
A study on community of phytoplankton in Diatas lake was conducted from April to September 2014. This study aimed to describe composition and structure of phytoplankton of the lake. We sampled phytoplankton at 6 stations purposively using plankton net that hauled vertically. We found 70 species of phytoplankton those belong to five classes, i.e. Bacillariophyceae (33 species), Chlorophyceae (27 species), Cyanophyceae (5 species), Dinophyceae (3 species) and Euglenophyceae (1 species). Total density of phytoplankton ranged from 881.06 to 3,196.02 ind/l. The highest density was at Station VI (Teluk Kinari) and the lowest one was at Station III (Muaro). Phytoplanktons with higher relative density (RD > 5 %) were Melosira italica, Synedra ulna, Melosira granulata (Bacillariophyceae), Staurastrum cereates, Chlorella vulgaris and Spirogyra fluviatis (Chlorophyceae). Shannon-Wiener Diversity index of phytoplankton (H`) ranged from 1.30 to 1.71 with the highest diversity index was at Station IV (Batang Hari) and the lowest was at Station V (central lake). Equitability index (E) was ranged from 0.39 to 0.57. Similarity index among stations were low which ranged from 34.48 to 62.50%.